VD_FINDINFO Jug / 2020 / 241 vom 11. Juni 2020 - VD Tribunal cantonal (2020)
RÉCUSATION, MOTIF DE RÉVISION, RÉVISIONDÉCISION, MINISTÈRE PUBLIC, ADMISSION DE LA DEMANDE | 413 al. 2 CPP (CH), 56 let. f CPP (CH), 58 CPP (CH), 60 CPP (CH)